EKSISTENSI KEKUASAAN TOYOTOMI HIDEYOSHI DALAM NOVEL TOYOTOMI HIDEYOSHI NO KEIEI JUKU KARYA KITAMI MASAO - Tias Haptari, Komang (Humanis; Volume 15. No.3. Juni 2016)
The title of this research is “The Existence of Power of Toyotomi Hideyoshi in Toyotomi Hideyoshi no Keiei Juku novel by Kitami Masao". This study aims to determine the existence of leadership and the collapse of the leadership of Toyotomi Hideyoshi. The theory used in this study is sociology literature according to Nurgiyantoro (2002), existentialism according to Sartre (in Hassan 1976), and theory of autocratic and autocratic leaders according to Terry (in Kartono 1983). The data of this study were analyzed by descriptive analysis method. Based on the analysis result, Toyotomi Hideyoshi in Toyotomi Hideyoshi no Keiei Juku novel had a strategies and actions to maintain his existence and superiority. Those strategies was able to take Toyotomi Hideyoshi to the supreme of power. After he reached the highest authority in Japan, Toyotomi Hideyoshi had an ambition to expand the territory to Korea and China. Eventually, leadership of Toyotomi Hideyoshi had collapse caused by his greed
Keywords: Existence, strategy, superiority, power